Pemodelan Fuzzy Inference System (FIS) dan Certainty Factor (CF) untuk Grading Ternak pada Penggemukan Sapi Bali - Arnaldy, Defiana; Seminar, Kudang B.; Muladno; Sukoco, Heru; Neyman, Shelvie Nidya (PETIR, 2025)
Beef cattle development in Indonesia has developed in several regions by applying livestock technology and innovation through the school for smallholder communities (namely SPR in Indonesian). The SPR program has been established in several regions in Indonesia and has had a positive impact on smallholder farming. The condition of livestock in each SPR is still classified as not having good productivity. One of the most important factors in developing livestock populations for breeding and fattening purposes is the availability of good seed sources based on good genetic quality. The grading classification of cattle for breeding and fattening purposes needs to be identified in detail and comprehensively, including through selection based on qualitative and quantitative traits. The main objective of this research is to develop a livestock grading model in Balinese cattle fattening using fuzzy inference system and certainty factor approach. Grading is done by looking at information from the morphometric characteristics of livestock. The method used in this research is quantitative and qualitative data collection with a system of direct interviews with farmers and measurements of their livestock. The parameters used follow the characteristics of animal morphometrics, namely body weight, body length, chest circumference, chest width, hip height, hip width, pelvic height, hip height. The results obtained from the initial data of the experiment show that the classification is divided into three classes, namely class I, class II, and class III.